A Community at Stake: The Mental Health Situation of Migrant Workers in Lebanon - Al Riachi, Rhea (2024)
The looming mental healthcare challenges in Lebanon, particularly across the migrant’s community, has contributed to increased inequalities in the host country. The dominant reasoning of this trend is the distressed economic situation, the inhumane regulations of the Kafala system and the lack of sustainable funds allocated for psychosocial support. Previous research publications have identified patterns of mental disorders among residents in Lebanon (citizens and foreigners), however it has been unable to segregate the data by nationality and gender across the migrant’s population. This thesis employs a dual conceptual framework, drawing on both social psychology and intersectionality. Through desk research and interviews with members of local and international organizations, the study decomposes the surge of the psychological challenges faced by domestic workers after the Beirut explosion and proposes action-oriented policy recommendations abreast the national constraints. In addition to desk reviews, seven interviews with key personnel and mental health experts, working with migrant groups in Lebanon, were conducted in person and online. This qualitative approach adds depth to the ongoing research work, offering a deeper understanding of lived experiences and challenges in the current context. Contrary to what has been assumed, lack of legal documents was at the core of preventing migrant workers from accessing mental healthcare services. Moreover, the correlation between mental healthcare, social cohesion and development remains overlooked in literature, particularly regarding the empowerment of domestic workers in Lebanon. Highlighting the main champion and spoiler stakeholders, this paper recommends collective efforts and coordination between various actors to implement short-term and long-term policy reforms, starting with the amendment of the Lebanese constitution and leading to the abolishment of the Kafala system. Finally, one to one therapy sessions and collective drama sessions were identified as the most effective therapeutic approaches for migrant domestic workers.